2014
DOI: 10.1177/1933719113492205
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ovarian Endometrioma on Expression of Steroid Receptor RNA Activator, Estrogen Receptors, Vascular Endothelial Growth Factor, and Thrombospondin 1 in the Surrounding Ovarian Tissues

Abstract: This study investigates the influence of ovarian endometrioma on expression of steroid receptor RNA activator (SRA), estrogen receptors (ERs), vascular endothelial growth factor (VEGF), and thrombospondin 1 (TSP-1) in the surrounding ovarian tissues. Taken from the women with ovarian endometrioma and mature teratoma during laparoscopy, the biopsies were analyzed by realtime polymerase chain reaction and Western blot. Our results indicated that ovarian tissues surrounding endometrioma had lower SRA and ER-a lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In our study, the most significant risk occurred in the subgroup of women with endometrioma. The hypotheses of alteration of ovarian endocrine functions in the presence of endometrioma or modifications of vascular growth factor expression such as vascular endothelial growth factor (VEGF) in the surrounding ovarian tissues could contribute to explaining our results (37,38).…”
Section: Discussionmentioning
confidence: 82%
“…In our study, the most significant risk occurred in the subgroup of women with endometrioma. The hypotheses of alteration of ovarian endocrine functions in the presence of endometrioma or modifications of vascular growth factor expression such as vascular endothelial growth factor (VEGF) in the surrounding ovarian tissues could contribute to explaining our results (37,38).…”
Section: Discussionmentioning
confidence: 82%
“…One study demonstrated that ovarian endometrioma increases SRA, SRAP, and ERs in the surrounding ovarian tissues, which may affect biological behaviors of this condition. 12 As distinct from the expressions of these molecules, another study showed an increase in SRAP and a reduction in ER-β expression during the malignant transformation from endometriosis to atypical endometriosis to clear cell carcinoma. 13 The data indicated that there is not always a positive relationship between the expressions of these 2 genes.…”
Section: Introductionmentioning
confidence: 98%
“…However, overexpression of VEGF receptors could be related to the accumulation of follicular fluid and abnormal follicular growth. In addition, VEGF is involved in other reproduction disorders, such as endometriosis [ 83 ]. It is found that the luteinizing hormone surge could trigger follicular maturation and ovulation by activating the MAPK14 signaling pathway in granulosa cells [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%